Heritable priming by Trichoderma: A sustainable approach for wheat protection against Bipolaris sorokiniana - Tiwari, Menka; Singh, Rajat; Jha, Rintu; Singh, Prashant (Frontiers in Plant Science, 2022)
Crop plants encounter a variety of biotic challenges in the field and face a significant reduction in crop yield. In the current scenario of an ever-increasing global population, there is an urgent need to protect plant health by using a sustainable approach to maximize crop productivity and mitigate food demands. Nowadays, we mostly rely on chemical crop protection techniques, which are causing a number of environmental and health difficulties. Defence priming is a chemical-free, eco-friendly, and sustainable strategy of crop protection, which is also called "green vaccination. In the present study, for the first time, we used Trichoderma as a priming agent to protect wheat crops from spot blotch disease. We have established Trichoderma mediated defence priming in wheat against Bipolaris sorokiniana for sustainable crop improvement. We have characterised the morphological, disease phenotype, biochemical and yield parameters of Trichoderma primed and non-primed wheat under disease pressure. Trichoderma primed plants were found to be more protected against Bipolaris sorokiniana as compared to non-primed plants. Biochemical studies indicated that there is no direct activation of defence after priming stimulus but the defence response was activated only after triggering stimulus in terms of enhanced defence metabolites in primed plants as compared to non-primed plants. In the present study, since the defence was activated only when required, that is under a disease pressure, there was no unnecessary allocation of resources towards defence. Hence, no yield penalty was shown in primed plants as compared to the control. We further evaluated the inheritance of the primed state to the next generation and found that progeny of primed parents also performed better than the progeny of non-primed parents under disease pressure in terms of protection from Bipolaris sorokiniana as well as yield performance. This strategy has the potential to protect crops without any yield penalty and cause environmental degradation. Our research findings indicate that Trichoderma-mediated defence priming could be an alternative approach for improving wheat productivity under biotic stress. To our best knowledge, this is the first documented report for the Trichoderma mediated defence priming and induced inheritance in wheat plants.